Impacto da Lei Sarbanes-Oxley sobre os ADR's brasileiros: análise empírica - Barros, Diogo Azevedo (2011)
This paper analyzes the impact of Sarbanes-Oxley on the return of the ADRs of Brazilian companies listed in the United States. For the present study we used an initial sample of 96 Brazilian companies in a daily data window during 2002.